2009
DOI: 10.1093/jat/33.9.610
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of 11-Nor-9-Carboxy-Δ9-Tetrahydrocannabinol in a Pregnant Woman Following Heavy, Chronic Cannabis Use

Abstract: Differentiating new intake of drugs-of-abuse from residual drug excretion may be difficult, especially following chronic drug usage and for drugs with long elimination half-lives such as cannabis. In the present case, cannabis was found in the urine of a young pregnant woman following heavy and chronic cannabis use. She was warned that if she continued using cannabis while pregnant she would be forced to be hospitalized. She was subjected to serial urine testing with 2-7-day intervals. Urinary 11-nor-9-carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…A screening method capable for quantification and confirmation of a variety of SC metabolites at concentrations relevant for clinical and toxicological investigations has been developed. Quantitative screening results are essential when a recent intake needs to be distinguished from residual drug excretion caused by a former intake and repeated samples are available from the same individual . Moreover, the access of quantitative methods is crucial in order to carry out pharmacokinetic studies (ie, to estimate half‐lives, peak concentrations, and detection times in urine).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A screening method capable for quantification and confirmation of a variety of SC metabolites at concentrations relevant for clinical and toxicological investigations has been developed. Quantitative screening results are essential when a recent intake needs to be distinguished from residual drug excretion caused by a former intake and repeated samples are available from the same individual . Moreover, the access of quantitative methods is crucial in order to carry out pharmacokinetic studies (ie, to estimate half‐lives, peak concentrations, and detection times in urine).…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of metabolites can be valuable when a recent intake needs to be distinguished from residual drug excretion from a former intake. This principle is well known after intake of cannabis, and various algorithms have been developed for this purpose . For synthetic cannabinoids some data exist on the urinary pharmacokinetics and excretion rate of the metabolites of JWH‐018 and JWH‐073, whereas for other compounds, very little is known.…”
Section: Introductionmentioning
confidence: 99%
“…THC: Δ9-tetrahydrocannabinol, THCCOOH: 11-nor-9-carboxy-Δ9-tetrahydrocannabinol, CC ratio: creatinine-normalized THCCOOH, FD: food deprivation, <LOD: below the 0.2 ng/ml limit of detection, <LOQ: below the 0.6 ng/ml limit of quantification. 1 Serum THC was below LOQ in participant D immediately after FD, but was present the following day, in the concentration shown in the table.…”
Section: Discussionmentioning
confidence: 92%
“…Our participants had serum THC levels in the 0-3.6 ng/ml range at the time of admission to the ward, which is similar to those described as 'baseline' in the Australian human study [13] and those previously reported in chronic THC: Δ9-tetrahydrocannabinol, THCCOOH: 11-nor-9-carboxy-Δ9-tetrahydrocannabinol, CC ratio: creatinine-normalized THCCOOH, EX: exercise, NA: not applicable, <LOQ: below the 0.6 ng/ml limit of quantification. 1 Due to phlebotic veins, blood sampling failed in participant C after exercise. 2 The baseline urine specimen from participant E was collected the day before the exercise intervention and not immediately prior to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…THC was not routinely tested with urine samples; due to the generally long period of positivity in urine toxicology results which can last several weeks or even months with chronic cannabis consumption (e.g. Westin et al 2009), these results would be of limited clinical relevance. For the present analysis, results were only counted if the woman provided at least one valid urine sample per week during the last trimester of pregnancy.…”
Section: Methodsmentioning
confidence: 99%